Soft and flexible poly(ethylene glycol) nanotubes for local drug delivery. Issue 18 (1st May 2018) - Newland, B.; Taplan, C.; Pette, D.; Friedrichs, J.; Steinhart, M.; Wang, W.; Voit, B.; Seib, F. P.; Werner, C.
Abstract : Soft/flexible PEG-based polymer nanotubes released doxorubicin over a sustained period and reduced tumor growth in a metastatic breast cancer model. Abstract : Nanotubes are emerging as promising materials for healthcare applications but the selection of clinically relevant starting materials for their synthesis remains largely unexplored. Here we present, for the first time, the synthesis of poly(ethylene glycol) (PEG) based nanotubes via the photopolymerization of poly(ethylene glycol) diacrylate and other diacrylate derivatives within the pores of anodized aluminum oxide templates. Template-assisted synthesis allowed the manufacture of a diverse set of polymeric nanotubes with tunable physical characteristics including diameter (∼200–400 nm) and stiffness (405–902 kPa). PEG nanotubes were subjected to cytotoxicty assessment in cell lines and primary stem cells and showed excellent cytocompatability (IC50 > 120 μg ml −1 ). Nanotubes were readily drug loaded but released the majority of the drug over 5 days. Direct administration of drug loaded nanotubes to human orthotopic breast tumors substantially reduced tumor growth and metastasis and outperformed i.v. administration at the equivalent dose. Overall, this nanotube templating platform is emerging as a facile route for the manufacture of poly(ethylene glycol) nanotubes.